2016
DOI: 10.1002/acm2.12015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the validation testing in MPPG 5.a “Commissioning and QA of treatment planning dose calculations–megavoltage photon and electron beams”

Abstract: The AAPM Medical Physics Practice Guideline (MPPG) 5.a provides concise guidance on the commissioning and QA of beam modeling and dose calculation in radiotherapy treatment planning systems. This work discusses the implementation of the validation testing recommended in MPPG 5.a at two institutions. The two institutions worked collaboratively to create a common set of treatment fields and analysis tools to deliver and analyze the validation tests. This included the development of a novel, open‐source software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, only 31% of the irradiations met a stricter criterion that also required adequate target coverage. The several factors associated with poor performance, such as complex delivery techniques, lack of image guidance, and errors in contouring and planning, Jacqmin et al [21] observed that tests 3 and 4 were found to be useful in the refinement of the MLC model parameters, such as the MLC transmission and dosimetric leaf gap.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 31% of the irradiations met a stricter criterion that also required adequate target coverage. The several factors associated with poor performance, such as complex delivery techniques, lack of image guidance, and errors in contouring and planning, Jacqmin et al [21] observed that tests 3 and 4 were found to be useful in the refinement of the MLC model parameters, such as the MLC transmission and dosimetric leaf gap.…”
Section: Discussionmentioning
confidence: 99%
“…Commissioning was performed following the tests described in the MPPG 5.a. guideline [ 17 ]. As part of the VMAT/IMRT recommended tests, this guideline advises planning, measuring, and comparing plans for both the Head and Neck and C-Shape mock cases of the TG-119 report, as well as performing the PSQA for at least two relevant clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…The AAPM Medical Physics Practice Guideline (MPPG) 5.a recommends checking the dose calculation accuracy of clinical plans during the commissioning of a TPS [ 17 ]. Although this recommendation refers to delivering the plan to a phantom with appropriate dosimeters enabling the user to compare planned and delivered dose distributions, a validated MC simulation system allows the dose to be accurately computed in the full three-dimensional (3D) patient geometry.…”
Section: Introductionmentioning
confidence: 99%